2017
DOI: 10.1111/nuf.12211
|View full text |Cite
|
Sign up to set email alerts
|

Professional nursing values: A concept analysis

Abstract: Further research is needed in the development and testing of professional nursing values theory, and the reassessment of values instruments. Core professional values that are articulated may help unify the profession and demonstrate the value of nursing to the public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
100
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 36 publications
4
100
0
10
Order By: Relevance
“…While personal values are shaped through natural life situations , professional values are associated with specific professional development. Altruism is one of the professional values that reflects the standard of nursing care . The conceptualisation of altruism as a value in nursing care in this review strives to describe what altruism is; in what situations does it appear; for what purpose is it used; and how is it practiced.…”
Section: Resultsmentioning
confidence: 99%
“…While personal values are shaped through natural life situations , professional values are associated with specific professional development. Altruism is one of the professional values that reflects the standard of nursing care . The conceptualisation of altruism as a value in nursing care in this review strives to describe what altruism is; in what situations does it appear; for what purpose is it used; and how is it practiced.…”
Section: Resultsmentioning
confidence: 99%
“…Bireysel değerler dürüstlük, doğruluk, iyilik, demokrasi, dayanışma, iyi niyet, dostluk, hoşgörü, sabır, sevgi, aile, ırkçılık, kültür, yurtseverlik ve özgürlük olarak tanımlanırken; hemşireliğin mesleki değerleri ise yararlılık, adalet, doğruluk, estetik, eşitlik, özgürlük, özgecilik (alturizm), insan onuru, gizlilik, adalet, karar vermede özerklik, bakımda hassasiyet ve doğruluk, bağlılık, insan ilişkisi, sempati, dürüstlük, bireysel ve mesleki yeterlilik, bütünlük, fedakârlık olarak tanımlanmıştır. [18][19][20] Yapılan çalışmalar, bireylerin değer ve tutumlarının davranışlarını etkilediğini göstermektedir. 13,[21][22][23] Aynı şekilde, hemşirelerin algıladığı profesyonel değerler de verdikleri sağlık bakımının kalitesini etkilemektedir.…”
unclassified
“…The nurses who work with low levels of autonomy may have unpleasant feelings regarding personal and professional experience (Sarkoohijabalbarezi, Ghodousi, & Davaridolatabadi 2017). Hao et al believe that socio-historical factors influence the autonomy of nurses (Hao et al 2014 review on nursing resources' autonomy showed that it has culturally different meanings, such as freedom from others' control, freedom in decision making (Schmidt & McArthur 2017), and professional responsibility (Galbany-Estragués & Comas d'Argemir 2017); therefore, autonomy is assumed differently in different contexts.…”
Section: Professional Socialization In Professional Autonomy Domainmentioning
confidence: 99%